Signally by Jump Bidding in Private Value Auctions - Ruqu Wang; Alan Gunderson (Queen's University, Department of Economics, 1998)
This paper examines how a bidder can benefit from jump bidding by using the jump bid as a signal of a high valuation which causes other bidders to drop out of the auction earlier than they would otherwise. The information contained in a jump bid must be sufficient to induce a discrete change in the bidding behaviour of the other bidders. In an auction for a single item, a jump bid signals both the identity and the high valuation of a bidder. The existence of a beneficial jump bid equilibrium requires a gap in the distribution of the jump bidder and her identity must be concealed. Concealing the identity of the bidders permits the jump bidder to signal more information through the jump bid and thus she can benefit more from it. In an auction for multiple items, the jump bid signals a high valuation by the jump bidder.
Keywords: D44; 330; Auction; Jump Bidding